A randomised, double-blind, placebo-controlled phase IIB clinical trial of repeated application of gene therapy in patients with cystic fibrosis. Issue 11 (22nd March 2013) - Alton, Eric W F W; Boyd, A Christopher; Cheng, Seng H; Cunningham, Steve; Davies, Jane C; Gill, Deborah R; Griesenbach, Uta; Higgins, Tracy; Hyde, Stephen C; Innes, J Alastair; Murray, Gordon D; Porteous, David J
Abstract : The UK Cystic Fibrosis Gene Therapy Consortium has been working towards clinical gene therapy for patients with cystic fibrosis for several years. We have recently embarked on a large, multi-dose clinical trial of a non-viral, liposome-based formulation powered for the first time to detect clinical benefit. The article describes the details of the protocol.